Concurrent Administration of Immune Checkpoint Inhibitors and Stereotactic Radiosurgery Is Well-Tolerated in Patients With Melanoma Brain Metastases: An International Multicenter Study of 203 Patients. Issue 6 (18th December 2022) - Lehrer, Eric J.; Gurewitz, Jason; Bernstein, Kenneth; Kondziolka, Douglas; Fakhoury, Kareem R.; Rusthoven, Chad G.; Niranjan, Ajay; Wei, Zhishuo; Lunsford, L. Dade; Malouff, Timothy D.; Ruiz-Garcia, Henry; Peterson, Jennifer L.; et al.
Abstract : BACKGROUND: Melanoma brain metastases are commonly treated with stereotactic radiosurgery (SRS) and immune checkpoint inhibitors (ICIs). However, the toxicity of these 2 treatments is largely unknown when administered concurrently. OBJECTIVE: To evaluate the risk of radiation necrosis (RN) with concurrent and nonconcurrent SRS and ICIs. METHODS: The guidelines from the Strengthening the Reporting of Observational Studies in Epidemiology checklist were used. Inverse probability of treatment weighting, univariable and multivariable logistic regression, and the Kaplan-Meier method was utilized. RESULTS: There were 203 patients with 1388 brain metastases across 11 international institutions in 4 countries with a median follow-up of 15.6 months. The rates of symptomatic RN were 9.4% and 8.2% in the concurrent and nonconcurrent groups, respectively ( P =.766). On multivariable logistic regression, V12 ≥ 10 cm 3 (odds ratio [OR]: 2.76; P =.006) and presence of BRAF mutation (OR: 2.20; P =.040) were associated with an increased risk of developing symptomatic RN; the use of concurrent over nonconcurrent therapy was not associated with an increased risk (OR: 1.06; P =.877). There were 20 grade 3 toxic events reported, and no grade 4 events reported. One patient experienced a grade 5 intracranial hemorrhage. The median overall survival was 36.1 and 19.8 months for the concurrent and nonconcurrent groups (log-rank P =.051), respectively. CONCLUSION: Concurrent administration of ICIs and SRS are not associated with an increased risk of RN. Tumors harboring BRAF mutation, or perhaps prior exposure to targeted agents, may increase this risk. Radiosurgical optimization to maintain V12 < 10 cm 3 is a potential strategy to reduce the risk of RN.